Potential Soursop Leaf Extract, Soursop Seeds and Mahogany Seeds for Grayak Caterpillar Control (Spodoptera litura L.) - Yanuwiadi, Bagyo; Leksono, Amin Setyo; H., Hiasinta Guruh; Fathoni, M.; Bedjo, Bedjo (Natural B, 2013)
This research objective is to compare the effect of extracts of soursop leave, sousop seed and mahogany seed on stop feeding, mortality and surviving of pupae and imago of army worm (Spodoptera litura L.). Army worm larvae were collected from Kebun Percobaan Muneng Research Field, Probolinggo and transferred to laboratorium for rearing and treatment. Soursop leaves, soursop seeds and mahagony seeds were extracted by aquades extraction method. Bioassays were conducted by using five concentration variation applied on 10 larvae by dipping method with twice replication. Observation of stof feeding was conducted every 2 hours during 24 hours. Whereas, observation on mortality was done every 24 hours during 168 hours. Result showed that the effect of soursop leave extract on the stop feeding and mortality was better than that of soursop and mahogany seed. This effect was started from 33.3% at 16 HAA (hours after application) increased to 46% at 24 HSA. Interestingly, the effect on survivality of pupae and imago was highest on the application of mahagony extract. The failure of pupation was 70%, and that of imago was 76.6%. This indicates that the effect of soursop leave extract is better for sort time application but on the long-term, the effect of mahogany seed is better than the others.Â